Medical image computing and computer assisted intervention -- MICCAI 2017. 20th International Conference, Quebec City, QC, Canada, September 11-13, 2017, Proceedings /: 20th International Conference, Quebec City, QC, Canada, September 11-13, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available